The imaginal and detailed nymphal characters of Cincticostella fusca (Kang & Yang, 1995) (Ephemeroptera: Ephemerellidae) - Zhang, Wei; Han, Na; Zhang, Min; Wang, Yin-Fang; Zhou, Chang-Fa (Zootaxa, 2020)
Among the 17 known species of the genus Cincticostella, only five of them have been reported as both nymphs and imagoes, which does not include the Chinese species C. fusca Kang et Yang (1995). Here the nymphs are redescribed and reared imagoes are reported for the first time, based on material collected from southeastern China. Morphologically, the nymph is unique because of its large body size, expanded genae, pale median stripe on the anterior of the head, and dark tarsi. The male imago can be differentiated from congeners by its large body size, pigmented forewings, and the mesothoracic scutellum having a pair of membranous lamellae. More importantly, its penes are distinct, being fused for most of their length and having complex ventral projections. Adults emerge in early spring (March to April).